Use of social media in the process of recruiting human resources - Sančanin, Branislav; Čerović, Slobodan (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Social networks are increasingly consolidating their place in the process of recruiting candidates for advertised vacancies, and organizations are encouraged to consider their implementation in their employment strategies so that activities in identifying top talent are cost-effective, targeted and competitive. It has almost become a rule that employers check so-called background information on candidates via social networks, while potential candidates also obtain information about employers from several sources. The aim of the research is the connection between different target groups in the process of recruiting candidates and different social media, on which job vacancies are posted, for each of the three different positions: manager, professional/technical level and intern. The research was conducted in the Republic of Serbia from May to June 2021; questionnaires were distributed in electronic form, with 133 respondents taking part. Twitter advertising is significantly and positively correlated to the recruitment of women and the elderly for managerial positions, while advertising on LinkedIn is also significantly and positively correlated to the recruitment of women to managerial positions. The results were almost identical for technical and professional positions. The most significant difference in the connection between the recruitment target groups and the social media, on which the vacancies are posted, was identified for positions intended for interns.